2020
DOI: 10.1101/2020.02.16.942904
|View full text |Cite
Preprint
|
Sign up to set email alerts
|

APCMutation marks an aggressive subtype ofBRAFmutant colorectal cancers

Abstract: AbstractBackground & AimsWNT activation is a hallmark of colorectal cancer. BRAF mutation is present in 15% of colorectal cancers, and the role of mutations in WNT signaling regulators in this context is unclear. Here we evaluate the mutational landscape of WNT signaling regulators in BRAF mutant cancers.MethodsWe performed … Show more

Help me understand this report
View published versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

5
9
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
4
2

Relationship

0
6

Authors

Journals

citations
Cited by 8 publications
(14 citation statements)
references
References 43 publications
5
9
0
Order By: Relevance
“… 24 Therefore, BRAF -mutated CRC harbored more RNF43 mutations and fewer APC alterations compared to BRAF wild-type CRC. 25 In addition, the mutual exclusivity between RNF43 and APC mutations in BRAF V600E-mutant CRC was consistently observed in our and others’ studies. 25 Fennell et al have shown that APC mutations could induce aggressive biological behaviors and poor prognosis in BRAF V600E-mutant CRC, whereas RNF43 mutations were associated with prolonged OS.…”
Section: Discussionsupporting
confidence: 81%
“… 24 Therefore, BRAF -mutated CRC harbored more RNF43 mutations and fewer APC alterations compared to BRAF wild-type CRC. 25 In addition, the mutual exclusivity between RNF43 and APC mutations in BRAF V600E-mutant CRC was consistently observed in our and others’ studies. 25 Fennell et al have shown that APC mutations could induce aggressive biological behaviors and poor prognosis in BRAF V600E-mutant CRC, whereas RNF43 mutations were associated with prolonged OS.…”
Section: Discussionsupporting
confidence: 81%
“…The model genes APC and BRAF were selected to demonstrate the utility of this presented pipeline. APC and BRAF mutation assessment have been useful and expedient in prognosis of CRC and their relative expression levels and mutational status have been implicated in treatment response 7,9 . In the present study our analysis of existing clinical datasets shows a significant reduction in APC mRNA expression levels that occurs in distinct anatomical regions of colon tumour tissue when compared to healthy colon tissue (Figure 3).…”
Section: Discussionmentioning
confidence: 99%
“…Two genes important in CRC are the tumour suppressor gene adenomatous polyposis coli (APC) and the oncogene B-Raf proto-oncogene (BRAF), implicated in CRC development 7,9 . The most common CRC activation pathway, which is responsible for 70-80% of all CRC diagnoses, is triggered due to inactivation of the tumour suppressor gene APC, which has an important role in the wnt signalling pathway, intercellular adhesion, cytoskeleton stabilisation, cell cycle regulation and apoptosis [10][11][12] .…”
Section: Introductionmentioning
confidence: 99%
“…The top three most statistically different genomic alterations specific to APC mut-CRCs were PTPRK-RSPO3 gene fusions (p = 1.3 x 10 -5 ), RNF43 mutations (p = 4.7 x 10 -5 ) and BRAF mutations (p = 1.9 x 10 -4 ). These genetic alterations have been identified in CRC previously with evidence for mutual exclusivity with APC mutations [27][28][29][30] . (The RNF43 mutation G659Vfs*41, which is associated with MSI CRCs, was not present in the tumors analyzed here 31 .)…”
Section: Wnt Signaling Mutations In Apc Mut-crcsmentioning
confidence: 95%